PCRMS: a database of predicted cis-regulatory modules and constituent transcription factor binding sites in genomes. (22nd April 2022) - Ni, Pengyu; Su, Zhengchang
Abstract: More accurate and more complete predictions of cis-regulatory modules (CRMs) and constituent transcription factor (TF) binding sites (TFBSs) in genomes can facilitate characterizing functions of regulatory sequences. Here, we developed a database predicted cis- regulatory modules (PCRMS) (https://cci-bioinfo.uncc.edu ) that stores highly accurate and unprecedentedly complete maps of predicted CRMs and TFBSs in the human and mouse genomes. The web interface allows the user to browse CRMs and TFBSs in an organism, find the closest CRMs to a gene, search CRMs around a gene and find all TFBSs of a TF. PCRMS can be a useful resource for the research community to characterize regulatory genomes. Database URL : https://cci-bioinfo.uncc.edu/